Language of typography in political posters: visual rhetoric in Indonesian electoral design - Reza Pahlawan (Indonesian Journal of Language, Space, and Visual Arts, 2026)
Background: The Indonesian electoral arena is saturated with posters, billboards, and digital visuals where typography and color play decisive roles in shaping political communication. Objective: The purpose of this research is to examine how typographic hierarchies, symbolic colors and fonts, and visual representations of leadership construct persuasive and ideological messages in Indonesian campaign design. Method: The study employs a qualitative, multimodal discourse analysis combining Typographic Discourse Analysis, Barthesian semiotics, and Critical Discourse Analysis on a corpus of posters, banners, and social media visuals from the 2024 presidential and legislative campaigns. Results: The findings reveal that typographic hierarchies consistently prioritize candidate names over party logos, signaling a personalization of politics; color and font combinations encode cultural values such as nationalism, religiosity, or modernity; and visual portrayals of leaders reinforce myths of morality, youthfulness, or decisiveness. Implication: The implication of this research is that electoral visuals actively participate in shaping democratic processes, offering both opportunities for political literacy and risks of reducing politics to symbolic spectacle. Novelty: This study contributes to the ways typographic and visual design elements operate as ideological resources that personalize political communication and shape voter perception within Indonesia’s electoral landscape.